DOA estimation of multiple speech sources by selecting reliable local sound intensity estimates. (1st December 2017) - Ding, Shaowei; Chen, Huawei
Abstract: Sound source DOA estimation using first-order differential microphone arrays (DMAs) has been demonstrated as a promising means for the applications where the size of arrays is restricted. The existing methods for DOA estimation of multiple speech sources with first-order DMAs, however, are shown sensitive to noise and room reverberation. To combat the problem, we propose a DOA estimation algorithm by exploring the redundancies of two orthogonal first-order DMAs in sound intensity measurement. In particular, the reliable time–frequency points for DOA estimation can be effectively singled out by the proposed algorithm and thus leads to better DOA estimation performance in noisy and reverberant environments. Moreover, the proposed algorithm has a closed form solution, and no time-consuming search process over spatial space is required. Simulation and real experimental results have demonstrated the effectiveness of the proposed algorithm.